Menumbuhkan Sikap Keterbukaan Terhadap Yang Lain: Perspektif Silang Budaya (Cross-Cultural) - Putra, Andi Eka (Universitas Islam Negeri Raden Intan Lampung, 2018)
Various perspectives in fostering an attitude of openness to others (the others). One of them is a cross-cultural or cross-cultural perspective. Cultural crossing or cultural crossing is a way of combining two or more cultural elements which are then crossed, grafted, mated or reconciled, so that new, fresh and creative cultures emerge. Cross-cultural studies were introduced by Edward Burnett Tylor and Lewis H. Morgan in anthropology which later developed into the realm of culture. Cross-cultural perspectives can now be applied freely to something that refers to anything about the comparison of cultural differences, including the comparison of religion. The main goal is to minimize conflict and build a co-existence or sincere openness with others.